Preparation of Lipid Nanoemulsions Incorporating Curcumin for Cancer Therapy - Songyot Anuchapreeda; Yoshinobu Fukumori; Siriporn Okonogi; Hideki Ichikawa (Journal of Nanotechnology)
The aim of this study was to develop a new formulation of a curcumin lipid nanoemulsion having the smallest particle size, the highest loading, and a good physical stability for cancer chemotherapy. Curcumin lipid nanoemulsions were prepared by a modified thin-film hydration method followed by sonication. Soybean oil, hydrogenated L-α-phosphatidylcholine from egg yolk, and cosurfactants were used to formulate the emulsions. The resultant nanoemulsions showed mean particle diameter of 47–55 nm, could incorporate 23–28 mg curcumin per 30 mL, and were stable in particle size for 60 days at 4°C. The cytotoxicity studies of curucumin solution and curcumin-loaded nanoemulsion using B16F10 and leukemic cell lines showed IC50 values ranging from 3.5 to 30.1 and 22.2 to 53.7 μM, respectively. These results demonstrated the successful incorporation of curcumin into lipid nanoemulsion particles with small particle size, high loading capacity, good physical stability, and preserved cytotoxicity.